An improved fix-length compensation method for electrical discharge milling using tubular tools. (January 2018) - Pei, Jingyu; Zhuang, Xiaoshun; Zhang, Lenan; Zhu, Yetian; Liu, Yebin
Abstract: Due to inevitable wear of electrodes in micro electrical discharge machining (μEDM), compensation of tools is of great importance to maintain machining accuracy. Among all of the compensation strategies, fix-length compensation method is one of the most efficient ways for cavity milling because large single layer thickness can be achieved. However, previous studies have shown that slots with triangle-shape cross section are formed, and extra processing has to be performed to remove the surface fluctuations, which degrade machining accuracy and lower total efficiency. To improve the traditional fix-length compensation method, in this work, the cylindrical tool is replaced by the tubular tool, and a truncated conic tool end is observed in experiments. An analytical model is then developed relating the truncated conic shape to fix-length compensation parameters. This analytical model is then used to determine the machining parameters, which correspond to a preset milling depth. The effects of key parameters on plane machining are predicted by the analytical model and verified through double slots machining experiments, which show high machining accuracy can be reached under any overlapping ratios and target depths. Finally, the presented machining method is further validated by machining a rectangular cavity and a cavity with a circular pattern. Machining results prove the depth accuracy of the proposed method can be controlled within 4 μm. Highlights: A fix-length compensation electrical discharge milling using tubular tools is proposed. The machining parameters can be pre-determined through an analytical model. A fully controlled high precision machining process can be realized.